EP909 Influence of intraoperative administration of ketorolac on the prognosis of ovarian cancer. (1st November 2019) - Luyckx, M; Verougstraete, C; Forget, P; Jouret, M; Waterkeyn, M; Grandjean, F; Baurain, J-F; Van Gossum, J-P; Squifflet, J
Abstract : Introduction/Background: Several studies suggest that oncological surgery induce an acute inflammatory response, and that it may exacerbate certain mechanisms related to tumor growth and eventual dissemination. We propose to investigates whether the administration of Ketorolac (Taradyl)®, a nonsteroidal anti-inflammatory drug, given intraoperatively during surgery for ovarian, tubal, or peritoneal cancer, influences disease free survival (DFS) and Overall survival (OS). Methodology: A Retrospective analysis of all the patients operated at Cliniques Universitaires Saint-Luc; Brussel between 2015 and 2017 for ovarian, fallopian tube or peritoneum cancer. All the patient were included from the UCLouvain Network of Gynaecological Oncology (UNGO), an academic network in Belgium for centralisation of the surgery for ovarian cancer patient. Results: Of the 90 patients who met the inclusion criteria, 68% received Ketorolac intraoperatively. Only age was statistically different between the two groups (p<0.05). FIGO stage, Residual disease, rate of primary surgery, neodjuvant chemotherapy was well balanced in the 2 groups. Intra-oprative administration of Ketorolac was statistically significantly associated with an improvement of the DFS (p=0, 006). The median DFS in the group receiving ketorolac is 27 months versus 16 months for patients who did not receive ketorolac. There is also a statistically significant impact of peroperative administration of Ketoroloac on the OS ((p=0.03). Conclusion: These results suggest that the intraoperative administration of Ketorolac during surgery for ovarian, tubal or peritoneal cancer has a positive effect on the risk of recurrence and median survival. Disclosure: Nothing to disclose.